The comparison of non-invasive blood pressure monitoring with brachial intra-arterial blood pressure monitoring in patients with severe pre-eclampsia - Jacobs, Samier (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed)--Stellenbosch University, 2014.